DAMPAK PANDEMI COVID-19 TERHADAP SOSIAL EKONOMI INDUSTRI JAMU (STUDI KASUS: IKM JAMU BIMA SEJAHTERA DI DESA MERDIKOREJO, KECAMATAN TEMPEL, SLEMAN, YOGYAKARTA) - Fifit Rizki Khoerunnimah; Ari Astuti; Artita Devi Maharani (JURNAL ILMIAH AGRITAS, 2022)
ABSTRACT The research aimed to know the social economic conditions of the IKM Jamu BimaSejahtera before and after the covid-19 pandemic. The basic methods in research usedquantitative descriptive methods and comparative analysis. Data collection techniques usedquestionnaires and interviews. Whereas, the method used was the cencus method with 29sampling. Hypothetical testing on this research was performed using t-test paired samples.Research has shown that the socio-economic conditions of the IKM Jamu Bima Sejahteraimproved after covid-19 pandemic, or as good as those before covid-19 pandemic. Factorsafffecting health indicators after covid-19 pandemic include risk concerns of exposure tocovid-19 at nursing facilities (hospitals, clinics, midwife, and medical centers) maintaininga health pattern of life, consuming herbs, and applying health protocols. Factors affectingeducational indicators after covid-19 pandemic include online learning that seemsineffective at time, energy, and cost. Factors affecting the income indicators after covid-19pandemic include increased public interest in herbal consumption, rising the price of herbalherbs, and government policies about social restrictions or local lockdown. Factors thataffected respondent income differences following covid-19 pandemic include capital,experience time, herbal flavor, and work’s day frequency.